Scanmarker Air wireless digital highlighter [library of things]. (Scanmarker, 2021)
Time saver- Scans 3000 characters per minute. Full line of text within one second! Create summaries faster than ever before; just slide your handheld scanning pen across a line of printed text and watch it appear instantly on your screen. Scans and translates over 40 languages - Super accurate and fast multilingual OCR text scanner ideal for students and professionals. Scan directly into any computer application of your choice eg. Word or into our intuitive mobile apps. Text to speech- The Scanmarker apps will read the text back to you in real-time while scanning! Aids with memorization and reading comprehension, and is an effective assistive tool for those with dyslexia or other reading difficulties. Ultraportable and convienent- Scan and edit on the go! Scanmarker Air's ultra-portable design lets you scan wirelessly using Bluetooth, from anywhere, to a computer, smartphone or tablet. Compatible with Mac & Windows computers, plus iOS & Android devices.